Large Igneous Provinces of the Southern Hemisphere: Isotopic Geochemistry and Plagioclase and Pyroxene 40Ar/39Ar Geochronology of the Kalkarindji, Karoo and Ferrar Provinces - Ware, Bryant Douglas (Curtin University, 2017)
To develop a comprehensive understanding of geological processes a multidisciplinary approach must be utilized. This PhD research contributes to the understanding of Large Igneous Provinces (LIPs) petrogenesis through an integrated geochemical and high precision geochronological approach. This study integrates geochemical analyses and unprecedented high-precision and sensitive 40Ar/39Ar geochronology to continue to push various geochronological techniques and LIP research to new horizons.